Trends in ozone, its precursors, and related secondary oxidation products in Los Angeles, California: A synthesis of measurements from 1960 to 2010. Issue 11 (13th June 2013) - Pollack, Ilana B.; Ryerson, Thomas B.; Trainer, Michael; Neuman, J. A.; Roberts, James M.; Parrish, David D.
Abstract: [1] Decreases in ozone (O3 ) observed in California's South Coast Air Basin (SoCAB) over the past five decades have resulted from decreases in local emissions of its precursors, nitrogen oxides (NO x = NO + NO2 ) and volatile organic compounds (VOCs). Ozone precursors have been characterized in the SoCAB with measurements dating back to 1960. Here we compile an extensive historical data set using measurements in the SoCAB between 1960 and 2010. Faster rates of decrease have occurred in abundances of VOCs (−7.3 ± 0.7% yr −1 ) than in NO x (−2.6 ± 0.3% yr −1 ), which have resulted in a decrease in VOC/NO x ratio (−4.8 ± 0.9% yr −1 ) over time. Trends in the NO x oxidation products peroxyacetyl nitrate (PAN) and nitric acid (HNO3 ), measured in the SoCAB since 1973, show changes in ozone production chemistry resulting from changes in precursor emissions. Decreases in abundances of PAN (−9.3 ± 1.1% yr −1 ) and HNO3 (−3.0 ± 0.8% yr −1 ) reflect trends in VOC and NO x precursors. Enhancement ratios of O3 to (PAN + HNO3 ) show no detectable trend in ozone production efficiency, while a positive trend in the oxidized fraction of total reactive nitrogen (+2.2 ± 0.5% yr −1 ) suggests that atmospheric oxidation rates of NO x have increased over time as a result of the emissions changes. Changes in NO x oxidation pathways have increasingly favored production of HNO3, a radical termination product associated with quenching the ozone formation cycle. Key Points: O3 reductions result from decreasing VOC and NOx abundances and VOC/NOx ratio Oxidation products show no detectable trend in ozone production efficiency Increased NOx oxidation rates increasingly favor HNO3 production over time